2, 2‐Bistrifluoromethyl‐4, 5‐difluoro‐1, 3‐dioxole‐co‐tetrafluoroethylene copolymers with different compositions: Synthesis, chain and condensed matter structures and optical properties. Issue 31 (2nd June 2022) - Yu, Dayang; Mao, Guoliang; Wang, Wenshuo; Cai, Huaixun; Wang, Shuhua; Pan, Pengju; Bao, Yongzhong
Abstract: Synthesis of 2, 2‐bistrifluoromethyl‐4, 5‐difluoro‐1, 3‐dioxole‐ co ‐tetrafluoroethylene (PDD‐TFE) copolymers with precise chemical structures and understanding effects of the structures on properties are essential for their application. Herein, PDD‐TFE copolymers with different average compositions and narrow composition distributions (NCDs) were synthesized and applied to study the influences of chemical structures on condensed matter structures and optical properties of copolymers. The average length of (PTFE ) n sequences were decreased from 7.62 to 1.63, and percentage of TFE in long (PTFE ) n sequences ( n > 5) decreased from approximately 50% to less than 1%, as PDD molar fraction in the copolymer ( F PDD ) increased from 13.24% to 52.22%. Consequently, the copolymer with F PDD = 13.24% was semi‐crystalline with a crystallinity degree of 11.57% (determined by WAXD), while the copolymer with F PDD = 52.22% was completely amorphous. The steric energies, glass transition temperatures and transparency of PDD‐TFE copolymers were increased as more cyclic and non‐coplanar structure PDD monomer was incorporated into the copolymers. Refractive indexes of PDD‐TFE copolymers were low and linearly decreased with the increase of F PDD . PDD‐TFE copolymers with high transparencies, low refractive indexes and other excellent properties can be successfully used in the optical fibers and semiconductor fields. Abstract : 2, 2‐Bistrifluoromethyl‐4, 5‐difluoro‐1, 3‐dioxole‐ co ‐tetrafluoroethylene copolymers with different NCDs were prepared and applied to study the influences of chemical structures on condensed matter structures and optical properties of copolymers.